Answer:
A horizontal translation of 5 units to the left.
Step-by-step explanation:
Given the parent linear function:
![\displaystyle f(x)=x](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%28x%29%3Dx)
To shift vertically n units, we can simply add n to our function. Hence:
![f(x)=x+n](https://tex.z-dn.net/?f=f%28x%29%3Dx%2Bn)
So, a vertical shift of 5 units up implies that n=5. So:
![f(x)=x+5](https://tex.z-dn.net/?f=f%28x%29%3Dx%2B5)
As given.
However, to shift a linear function horizontally, we substitute our x for (x-n), where n is the horizontal shift. So:
![f(x-n)=(x-n)](https://tex.z-dn.net/?f=f%28x-n%29%3D%28x-n%29)
Where n is the horizontal shift.
For example, if we shift our parent linear function 1 unit to the right, this means that n=1. Therefore, our new function will be:
![f(x-1)=(x-1)](https://tex.z-dn.net/?f=f%28x-1%29%3D%28x-1%29)
Or:
![f(x)=x-1](https://tex.z-dn.net/?f=f%28x%29%3Dx-1)
We notice that this is also a vertical shift of 1 unit downwards.
Therefore, we want a number n such that -n=5.
So, n=-5.
Therefore, it we shift our function 5 units to the left, then n=-5.
Then, our function will be:
![f(x-(-5))=(x+5)\text{ or } f(x)=x+5](https://tex.z-dn.net/?f=f%28x-%28-5%29%29%3D%28x%2B5%29%5Ctext%7B%20or%20%7D%20f%28x%29%3Dx%2B5)
Hence, we can achieve f(x)=x+5 from f(x)=x using a horizontal translation by translating our function 5 units to the left.